Carl Jung and the Ghosts. (2nd October 2021) - Richter, Claudia
Abstract : This essay explores Carl Gustav Jung's approach to paranormal phenomena. It sets out by looking at two of Jung's personal experiences with ghostly phenomena and his explanations of them, followed by an overview of the most relevant aspects of Jung's lifelong interest in the supernatural. Special attention is given to notions of sensitivity and prerational cognition in the context of Jung's struggle with the Cartesian worldview, which includes a look at the Romantic philosopher of nature, Gotthilf Heinrich von Schubert.